A new azadirachta from the crude extracts of neem (Azadirachta Indica A. Juss) seeds. Issue 15 (3rd August 2017) - Gao, Quan; Sun, Jia; Xun, Hang; Yao, Xi; Wang, Jin; Tang, Feng
Abstract: One new compound, 2H, 3H-cyclopent[b] furo [2′, 3′:4, 5] naphtho [2, 4-d] heptlactone-[3, 7] furan-6aceticacid, 3-(acetyloxy)-8-(3-furyl)-2a, 4a, 4b, 4c, 5, 5a, 6, 6a, 8, 9, 9a, 10a, 10b-13 hydrogen-2a, 5a, 6a, 5-tetramethyl-3-[[(2E)-2-methyl-1-oxo-2-butenyl]oxy]-methyl ester, named azadirachta R (1 ), along with 10 known ones, Azadirachta A, AZ-B, AZ-D, AZ-H, AZ-I, nimbin, deacetylnimbin, salannin, deacetylsalannin and azadiradione were isolated from the crude extracts of neem ( Azadirachta indica A. Juss) seeds, which were determined by UV, IR, HR-ESI–MS and NMR data analyses. According to the in vitro antibacterial activity experimental results, this compound showed good antibacterial activity to two bacteria, the minimum inhibitory concentration and the minimum bactericidal concentration of compound1 to two kinds of bacteria are 50 and 25 mg/L, respectively, which were determined by resazurin colour-micro-dilution method. The experimental results provide a theoretical basis for the comprehensive utilisation of azadirachtin compounds in the future. Abstract :